ASSESSMENT OF THE HEAVY METAL DISTRIBUTION IN SOILS WITHIN THE AREASFOR THE MUNICIPAL SOLID WASTE DISPOSAL - Azimov, O.; Kuraeva, I.; Bakhmutov, V.; Voytyuk, Yu.; Karmazynenko, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aim of the study was to identify the ecological negative impact of municipal solid waste Landfill № 5 located near the city of Kyiv on the environment. The complex geoecological studies are carried out within the area. They included the field works with the sampling of different elements of landscape (soil, surface water, vegetation) and the further laboratory and geochemical analyses. The acute pollution with copper-zinc of soils has been detected. Moreover, in vicinity of the north-eastern contour of Landfill area the anomalies for Cu content (10000 mg/kg that is in 300 times higher than the maximum allowable concentrations – MAC), Zn content (5000 mg/kg that is in 90 times higher than the MAC), Pb content (1000 mg/kg that is in 30 times higher than the MAC) are revealed in the samples taken from the surface soil layer of 0–5 cm. These soil samples are characterized by maximal specific magnetic susceptibility (572.1 SІ10-8 m3/kg). The heavy-metal contamination of soil has shown that their mobility increased tenfold in comparison with the background sites. The elements of significant accumulation in the grass vegetation are Cu and Cr at the biological absorption coefficients of 1.25 and 1.0, respectively. The contents of analyzed chemical elements and compounds in the surface water samples taken from the background sites don't exceed the MAC. The indicated results characterize the scientific novelty of the studies. Their practical significance is the making management decisions by the administrative authorities with regard to the further waste facilities maintenance.
Keywords: Landfill; solid waste; heavy metals; soil; geochemical analysis